Peningkatan Pembelajaran Menulis Argumentasi melalui Model Pembelajaran Brainstorming - R.Q., Rangga Tina; Gani, Erizal; Nursaid, Nursaid (Universitas Negeri Padang, 2013)
The purpose of this article is to explain the process and the improvement of learning outcomes argumentation writing skills aided brainstorming class X.1 SMA Negeri 2 Tebo that is viewed from four argumentation writing assessment indicators, that are make sure the reader, proof the turth, change the mind of reader, and show the fact. Based on the research’s results it can be concluded that the application of brainstorming can improve the process and learning outcomes argumentation writing skills of students of class X.1 SMA Negeri 2 Tebo. It can be seen in the significant average of mark. In preliminary observations (pre-cycle) the average is 39,16% then in first cycle is 52,67%, the second cycle is 75,67%.